(untitled) (diségno, 2018)
The paper illustrates the scientific assumptions and the results of a didactic activity aimed to explore the potential of interactive and immersive dynamic perspectives by experimenting with new virtual reality applications for the enhancement of cultural heritage. In particular the study focuses on the enhancement of some European sociological science fiction movies. In this sense, immersive virtual reality, experimentally, has been used to realize and explore models capable of representing the quality of the space and emotional conditions present in the selected movies.